Performance inspection and defect cause analysis of girth weld of high steel grade pipeline. Issue 1 (1st April 2022) - Xu, Yan; Wu, Mingchang; Nie, Xianghui; Feng, Zhenjun; Li, Liang; Yang, Fengping
Abstract: The suspected circumferential weld defects found in the pipeline inspection process were tested and studied. It was found that there was slag inclusion in the girth weld at 9 o'clock, which had not been found in the early stage or in the laboratory nondestructive testing process. The defects are most likely due to incomplete slag removal between layers and low welding wire energy. There was a root crack at the 6 o'clock position of the weld, and the crack length was 10 mm, which was close to the original film and the detection result of excavation. The misjudgment of the field rebeat and the laboratory test results may be caused by the pits in the weld cover and the bottom weld. The crack is caused by the crystal crack formed along the middle of the columnar crystal during the solidification process of backing welding due to the increase of residual stress caused by the reduction of welding layers and the group stress caused by the steel tube.